Auditor Selection Process: An Interplay of Demand Mechanisms – A Multilevel Network Approach. Issue 1 (1st January 2021) - Kacanski, Slobodan; Lusher, Dean; Wang, Peng
Abstract: Studies on demand side mechanisms related to experience goods argue that demand is driven by recommendation and reputation. In an auditing context, research showed that both of these mechanisms play an important role in determining partner selection, however, only when the mechanisms are observed in isolation. On this basis, this study raises a concern about whether the mechanisms are mutually exclusive, and if not, how does recommendation and reputation in auditor selection context create an interplay in the process of auditor selection. We test our hypotheses on network data of Danish public companies. Findings from the social network study indicate that auditor selection is a sensitive and complex task for boards of directors, as it is not only driven by either of the mechanisms. Rather, partner selection is driven by the combination of both recommendation and reputation, which creates the interplay and, thus, indicates that the demand mechanisms are not mutually exclusive and should not be observed in isolation of one another.